INNOVATIVE APPROACHES TO THE PROCESS OF STUDENTS' SELF-EDUCATION: THEORY AND PRACTICE - Sadullayeva Zarnigor (Modern American Journals, 2025)
The article covers the theoretical and practical aspects of using innovative approaches in the process of students' self-education. In the context of globalization and digital transformation, the development of independent thinking, creativity and initiative has become an urgent task for higher educational institutions. The study analyzes the effectiveness of methods such as coaching, mentoring, peer-to-peer learning, problem-based learning, digital platforms and gamification. Based on statistical data, Uzbek and international experiences are comparatively studied, and it is emphasized that motivation, reflection, digital technologies and social support factors play an important role in the process of students' self-education. The results show that innovative approaches actively involve students in personal development, increasing the efficiency and competitiveness of the higher education system.
Keywords: self-education, innovative methods, coaching, mentoring, peer-to-peer learning, problem-based learning, digital platforms, gamification, motivation, reflection.